The Development of Educational Animation Videos Using the Capcut Application in Pancasila Education Subject at SDN 01 Padang Laweh - Sukron, Muhammad; Asmara, Dwi Novri; Utari, Juwita Dwi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the finding that the learning process is still not optimal, with students showing a lack of interest in the learning process, especially in Pancasila Education content, due to the fact that the teaching of Pancasila Education mainly involves lectures or storytelling. Therefore, the researcher concluded that in Pancasila Education learning, it is necessary to utilize engaging and creative learning media to prevent students from feeling bored or monotonous during the learning process. One such media is animated video, which is considered appropriate and supportive for creating an engaging learning environment that captures students' attention. This would make it easier for students to understand the material and enhance their active participation in the learning process. This study is a research and development (R&D) type of research. The development model used is the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The trial was conducted in class VI at SDN 01 Padang Laweh, with data collection techniques through analysis of validity, practicality, and effectiveness tests. The results of the validation of the animated video learning media obtained an average language validation score of 96%, categorized as very valid. The validation results for the teaching module received an average of 84.37%, categorized as very valid, while the validation results for the questions obtained an average of 92.18%, also categorized as very valid. The results of the practicality test conducted by educators and students in class VI showed a score of 90.76%, categorized as very practical. The effectiveness test, measured through the students' learning outcomes, showed an average score of 84%, categorized as highly effective.